PERCEPTIONS AND PRACTICES OF TRANSLANGUAGING IN INDONESIAN EFL CLASSROOMS: EXPLORING TEACHERS' VIEWS AND IMPLEMENTATION STRATEGIES - Kukuh Tri Laksono; Sumardi; Kristian Adi Putra (Universitas Muhammadiyah Makassar, 2025)
In Indonesian multilingual classrooms, students come to the classrooms with the ability to speak more than one language. Previous studies have highlighted that teachers should view the languages as resources for learning, instead of problems. In this context, translanguaging emerges as a relevant and pedagogical approach to be implemented. This study investigates the perceptions of three Indonesian English as a Foreign Language (EFL) teachers about translanguaging, the kinds of translanguaging that they implemented, and the ways they dealt with the challenges. A case study was employed, with the data collected through a series of semi-structured interviews and multiple classroom observations from three purposely sampling EFL teachers. Thematic analysis was applied to identify the patterns in the data. Findings reveal that teachers viewed translanguaging positively, as it aided comprehension and improved students’ confidence by providing linguistic support in students' native language. The forms of translanguaging included translation, code-switching, code-mixing, and transliteration, with code-mixing being the most frequent and transliteration was not found. All these findings highlight the importance of implementing translanguaging pedagogical strategies that actively promote multilingualism in the classrooms. This study offers the ways in which teachers could implement such strategies and provides directions for further research.